KEEFEKTIFAN BEBERAPA HERBISIDA CAMPURAN DALAM MENGENDALIKAN GULMA UMUM PERKEBUNAN KELAPA SAWIT - Nopiansyah Nopiansyah; Edi Syahputra; Sarbino Sarbino (Fakultas Pertanian Universitas Tanjungpura, 2021)
Herbicide mixing technology is an opportunity to improve efficiency and control weeds. This study aimed to develop the effectiveness of a mixed herbicide (tank mix) between the active ingredient formulations of tiafenacil, glyphosate, methyl metsulfuron, and paraquat dichloride in controlling common oil palm weeds. The research was carried out for approximately 3 months, from January to March 2021, in oil palm plantations. The research used was a randomized block design with 9 treatments and 4 replications. Herbicide application using a knapsack sprayer and a red nozzle. Spraying is carried out on weeds in the oil palm weed circle. Vegetation analysis was carried out before the application of herbicides, the percentage of mortality was observed 3,7, 14, 21, and 30 days after spraying and weed regrowth was carried out 30, 45, and 60 days after spraying. The results showed that the paraquat mixture of tiafenacil was able to increase the effectiveness of the herbicide against common weeds compared to the single herbicide tiafenacil at doses of 2 l/ha and 4 l/ha based on mortality. The paraquat mixture in methyl metsulfuron was able to increase the effectiveness of the herbicide against common weeds compared to the single herbicide methyl metsulfuron based on its mortality. The single herbicide tiafenacil dose of 2 l/ha was able to suppress the dry weight of Ottochloa sp better than the single herbicide tiafenacil dose of 4 l/ha. The mixture of methyl metsulfuron in tiafenacil was able to suppress the dry weight of Asystasia sp better than the single herbicide tiafenacil at a dose of 2 l/ha.